A Study of ICT Adoption and its Impact on Selected MFIs of Gujarat - Bhatt, Nityesh; Patel, Ritesh; Kaur, Amandeep (Indian Journal of Finance, 2020)
The microfinance sector is considered as an important vehicle for financial inclusion in developing countries, including India. Despite significant efforts by various microfinance institutions (MFIs) and Government of India, microfinance penetration has grown little over 50% of the Indian population. Information and communication technology (ICT) has changed the scope and functioning of the microfinance industry and can play a catalytic role in its pursuits of social objective and sustainability. This paper presented a brief overview of the microfinance sector in India. It focused on the role of ICT in strengthening MFIs' operations. The Government of India’s role in digital enablement was also discussed. Primary research was also conducted with the aim to study the adoption of ICT and measure its impact on the performance of selected MFIs of Gujarat State. It was found that ICT has been largely adopted by the MFIs and it was found to be beneficial for the core functions of the selected MFIs. However, there were some constraints in the adoption of ICT that need to be addressed.